FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA PADA KOPERASI KARYAWAN PT SOCFIN INDONESIA - hasibuan, santi mariya; Sriwardany, Sriwardany (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
This study aims to determine the effect of member loans, member deposits, and capital on the Remaining Operating Results (SHU) in PT Socfin Indonesia's employee cooperative. The research method used is quantitative descriptive research. The data obtained in this study are secondary data. The number of samples used was 60 samples. The sampling technique is carried out using the Purposive Sampling technique, which is the determination of samples with certain considerations. The data analysis test uses multiple linear regression analysis test using the help of SPSS 21. The results of this study show that simultaneously member loans, member deposits and capital have a significant effect on the remaining operating results of PT Socfin Indonesia's employee cooperative. Persial, variable member loans negatively affect the remaining operating results, and member deposits and capital have a positive effect on the remaining operating results of PT Socfin Indonesia's employee cooperative.